Developing Student's Notion of Measurement Unit For Area - Yuberta, Kurnia Rahmi; Zulkardi, Zulkardi; Hartono, Yusuf; Galen, Frans van (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Many researchers found that students have difficulties in understanding area measurement. Students mostly focus on applying formula to find the area of certain shapes without knowing what the area is and why the formula works. It is important for the students to know what attribute being measured and to construct the unit for area measurement.Â Therefore, the aim of this research is to develop activities that support students to know the attribute of area and the notion of measurement unit in learning area measurement. For this purpose, design research is chosen for achieving the research goal. Realistic Mathematics Education (RME) underlies the design of context and activities. A teacher and students in grade 3 in elementary school (SDN 21) in Palembang Indonesia will be involved in this research.Keywords: Area measurement, unit, design research, RME